Fred R. McCrumb papers - McCrumb, Fred R. (Fred Rodgers), 1925-1976.
Correspondence, speeches, articles, abstracts, bibliographies, reports, surveys, studies, protocols, topical files, notes, biographical material, printed material, and other papers relating chiefly to McCrumb's career as professor and administrator at the University of Maryland at Baltimore School of Medicine including his administration of a tropical medicine research center in Lahore, Pakistan, and of rubella vaccine field testing. Topics include eradication of malaria, eradication of smallpox in Pakistan, microorganisms and related diseases, and communicable diseases and their causative agents. Correspondents include Herbert C. Barnett, Kenneth O. Courtney, Eugene J. Gangarosa, Christian R. Klimt, Theodore E. Woodward, Parke, Davis & Company, and Philips Roxane, inc.
Physician, epidemiologist, and medical administrator.
Finding aid available in the Library of Congress Manuscript Reading Room.
Keywords: Barnett, Herbert C. -- Correspondence; Courtney, K. O. -- Correspondence; Gangarosa, Eugene J. -- Correspondence; Klimt, Christian R. -- Correspondence; Woodward, Theodore E. -- 1914- -- Correspondence; Parke, Davis & Company -- Correspondence; Philips Roxane, inc. -- Correspondence; University of Maryland at Baltimore. -- School of Medicine; Communicable diseases; Malaria -- Prevention; Medical colleges -- Maryland -- Baltimore; Medicine -- Research; Pathogenic microorganisms; Rubella vaccines; Smallpox -- Pakistan -- Prevention; Tropical medicine -- Pakistan -- Lahore; Epidemiologists; Administrators; Physicians